2018
DOI: 10.1111/joim.12772
|View full text |Cite
|
Sign up to set email alerts
|

Association of objectively measured physical activity with brain structure: UK Biobank study

Abstract: In summary, physical activity may play a role in the prevention of neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 21 publications
7
57
1
1
Order By: Relevance
“… 10 , 26 Our results are consistent with a study in the UK Biobank that observed significant associations only in participants younger than 60 years. 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 26 Our results are consistent with a study in the UK Biobank that observed significant associations only in participants younger than 60 years. 17 …”
Section: Discussionmentioning
confidence: 99%
“… 12 Furthermore, cross-sectional epidemiologic studies have established an association of physical inactivity with brain aging. 4 , 13 , 14 , 15 , 16 , 17 , 18 However, further work is needed to pinpoint the optimal dosage (duration × intensity) of PA needed to promote healthy brain aging. Although this question cannot be fully addressed in an observational study, our investigation sheds light on the dosage of PA most strongly associated with favorable brain structure in a community setting.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, more than 80% of reviewed studies did not control for lifestyle differences. Physical activity may impact brain structures and functions [93,94]. Given that patients with ME/CFS have to reduce their daily activities because of fatigue, objective measurement of physical activity in both patients and controls is essential to differentiate between brain differences that are unique in ME/CFS and those due to reduced physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this association was only observed within the group of participants over 51 years of age. In line with this, positive associations have previously been reported between total gray matter volume and sensor-measured physical activity, but only among adults over 60 years of age (Hamer et al, 2018). Further, while evidence of the positive long-term effects on cognition and the brain of MVPA is moderately strong among adults aged 50 years or older, the evidence is insufficient among adults younger than 50 years of age (Physical Activity Guidelines Advisory Committee, 2018).…”
Section: Figure 3 | (A)mentioning
confidence: 77%